The role of soy in development of breast, ovarian, endometrial and prostate gland cancer - Marcela Maksymowicz; Piotr Machowiec; Natalia Baran; Małgorzata Piekarska (Kazimierz Wielki University, 2021)
Introduction and purpose Soy as a rich source of isoflavones has become a focus of interest because of its positive health benefits on numerous diseases, particularly hormone-related cancers. The aim of this study was to present the current state of knowledge on the role of soy in the development of breast, ovarian, endometrial, and prostate gland cancer. A brief description of the state of knowledge Soy components reduce inflammation, stress oxidative and inhibit proliferation of breast, ovarian, endometrial, and prostate cancer cells. Isoflavones such as genistein, daidzein, S-equol via activation of estrogen receptors, inhibit aromatase synthesis and may decrease the risk of estrogen-dependent cancers. Moreover, soy food products have the potential toregulate molecular pathways of AR and reduce testosterone levels. It leads to a reduced risk of prostate cancer. Furthermore, increased consumption of soy protein and isoflavones decreased the risk of mortality from cancers. Conclusions Soy foods and their isoflavones are associated with reduced carcinogenesis. A higher amount of soy intake can have positive benefits for prevention of cancers including breast, prostate gland, endometrial and ovarian cancer.